2003
DOI: 10.1258/095646203767869174
|View full text |Cite
|
Sign up to set email alerts
|

One-and-a-half decades of HIV/AIDS in Tamil Nadu: how much do patients know now?

Abstract: Tamil Nadu has experienced the impact of HIV/AIDS for one-and-a-half decades and is considered a trailblazer in India in terms of combating the infection. So what are the knowledge levels among 292 HIV patients at Government Hospital for Thoracic Medicine and Christian Medical College? Latent class analysis revealed that it was not adequate. Television and peer contact were found to be most effective as source of knowledge for HIV. Patients who were in contact with health personnel might be expected to have mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Latent class analysis is a "respondent-centered" approach that seeks to group individuals into class groups based on their responses to a set of observed variables (in this case, responses to eight stigma statements which relate to stigma against PLHIV)[29]. Latent class analysis has been used widely in market research to tailor marketing campaigns to segments of the population as well as to understand patterns of complex health risk behaviors [30], including substance abuse [31], mental health [32,33], as well as HIV/AIDS risk behavior, knowledge and programming [10,32,34-36]. In addition to understanding the pattern of stigmatizing attitudes present in each class by examining the probability of each answer to the stigma statements on which the classes were composed, factors independently associated with the stigma class membership can be identified through latent class regression [29].…”
Section: Introductionmentioning
confidence: 99%
“…Latent class analysis is a "respondent-centered" approach that seeks to group individuals into class groups based on their responses to a set of observed variables (in this case, responses to eight stigma statements which relate to stigma against PLHIV)[29]. Latent class analysis has been used widely in market research to tailor marketing campaigns to segments of the population as well as to understand patterns of complex health risk behaviors [30], including substance abuse [31], mental health [32,33], as well as HIV/AIDS risk behavior, knowledge and programming [10,32,34-36]. In addition to understanding the pattern of stigmatizing attitudes present in each class by examining the probability of each answer to the stigma statements on which the classes were composed, factors independently associated with the stigma class membership can be identified through latent class regression [29].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread realization that ignorance is a significant contributor to the spread of HIV/AIDS has led to a large literature in India that has tried to assess the extent of people's awareness and knowledge of the disease. This includes the studies by Izhar (1990) on data from Aligarh town and Srinagar city, Balk & Lahiri (1997) on 30,000 ever-married women in thirteen HIV-prone Indian states, Sachdev (1998) on Delhi university students, Lal et al (2000) on college students in Kerala, Hawkes & Santhiya (2002) on sexually transmitted infections in India as a whole, Kattumuri (2003) on HIV/AIDS patients in Tamil Nadu, Pallikadavath et al (2005) on rural women in Maharashtra and Tamil Nadu, and, recently, by Bloom & Griffiths (2007) on women from three culturally contrasting states of Karnataka, Kerala and Tamil Nadu. The results are varied and region-specific but the overall message from these studies is that, while knowledge of the disease in India remains quite low and grossly inadequate, the level of awareness is alarmingly low for rural women, who are particularly vulnerable to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Indian women know comparatively less about HIV/AIDS than men. In community-based studies, men were found to be more informed than women among undergraduate students in Kerala (Lal et al, 2000), patients in Tamil Nadu (Kattumuri, 2003), college students in Pune (Singh et al, 1997) and university students in Delhi (Sachdev, 1998).…”
Section: Introductionmentioning
confidence: 99%